Problems of Adherence to Drug Therapy in Medical Rehabilitation - Isakova D.Z.; Valieva Z. S (Zien Journals, 2023)
Compliance is defined as “patient compliance with the treatment regimen and regimen.” Low compliance is a complex problem that can have both internal and external causes. It is customary to distinguish four groups of reasons: patient-related factors; therapy-related factors; factors associated with the doctor and factors associated with the environment (social aspect).
Keywords: Medical rehabilitation; compliance; drug therapy; adherence